A Naturalistic Study Of Teaching Writing To The Eighth Grade Students In SMP N 1 Sambi 2016/2017 Academic Year - Pratama, Dicky Aditya; , Mauly Halwat Hikmat, Ph.D (2017)
This research aims at describing a naturalistic study of teaching writing to the eighth grade Student's at SMPN 1 Sambi in 2016/2017 Academic Year which includes the objective teaching writing, the material used by the teacher to teach writing, the procedures of teaching writing, the kinds of classroom technique used by teacher to teach writing to the eight grade students at SMP N 1 Sambi in 2016/2017 academic year, and the problems faced by the teacher in teaching writing to the eight grade students at SMP N 1 Sambi in 2016/2017 academic year.The research is qualitative research. The subject of the study is the eighth grade students class D at SMP N 1 Sambi which consists of 32 students. The object of the study is teaching writing to the eighth grade student's at SMPN 1 Sambi in 2016/2017 Academic Year. The methods of collecting data are observation, interview, document analysis. The technique for analyzing data are data reduction, data display, and conclusion and verification. The findings show that the objective of teaching writing is the students can to express the idea in the functional text and short simple essay in the form of descriptive and recount, to interact with the surrounding environment. The materials for teaching writing are taken from student's book flying start, Start Your Journey for Junior High Scool Year VIII, by Lindsey-Clark from Esis. The Procedure for teaching writing consist of 1)pre writing,2)drafting and responding,3)sharing and responding, and 4)revising. The technique used are control free technique and free writing technique .The Problem faced by the teacher are class mangement, limited time, and different capability of the students. Key Words : describe of teaching writing, objective ,material, procedure, kinds of classroom techniques, problem faced by teacher.